REALIZATION OF RHYTHM IN POETRY “HUJAN BULAN JUNI” BY SAPARDI DJOKO DARMONO - Yusuf Adi Saputro; Yusi Anggraeni; Ida Lisdawati (IKIP Siliwangi, 2019)
The study aimed to determine the rhythm of the poetry The present study examined rhythm performed by the rhythm in the transcript of poetry Sapardi Djoko Darmono, title